2015
DOI: 10.1177/1060028015588127
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Pharmacological Treatment for Osteoporosis Among Patients Qualified for Pharmacotherapy According to the National Osteoporosis Foundation Guidelines

Abstract: Less than one-fourth of the population who should be considered for pharmacotherapy received osteoporosis treatment. Clinicians should be more aware of the unmet need for medication treatment for osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…We found low rates of osteoporosis medication use in both men and women diagnosed with osteoporosis, but it was especially low among men. Osteoporosis medication use rates were found to be 44.3–42% in women and 25.2–24.5% in men in this study, which were on the higher end compared to what was found in the literature . Even after adjusting for age and other characteristics, the probability of an elderly man with diagnosed osteoporosis being treated with evidence‐based pharmacotherapy was just 20% of that in women.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…We found low rates of osteoporosis medication use in both men and women diagnosed with osteoporosis, but it was especially low among men. Osteoporosis medication use rates were found to be 44.3–42% in women and 25.2–24.5% in men in this study, which were on the higher end compared to what was found in the literature . Even after adjusting for age and other characteristics, the probability of an elderly man with diagnosed osteoporosis being treated with evidence‐based pharmacotherapy was just 20% of that in women.…”
Section: Discussioncontrasting
confidence: 73%
“…Men are not only less likely to be diagnosed with osteoporosis than women, and men are also treated less often than women even when diagnosed with osteoporosis. The prevalence of osteoporosis medication use ranges from 7.1 to 27% in men compared to 4.6 to 50% in women despite the fact that osteoporosis treatment guidelines recommend initiation of pharmacologic therapy in both men and women who have bone mineral density (BMD) T‐scores ≤−2.5 at the femoral neck or spine by dual‐energy x‐ray absorptiometry (DXA) and those who have experienced fragility fractures . The lower medication use rate in men may be owing to the lack of awareness of osteoporosis and its consequences in men .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Current prevention methods focus on patient education, exercise programs, and antiresorptive pharmacotherapy. 3,4 Cement reinforcement of the femoral neck has also been suggested as prevention for osteoporotic fractures. 5,6 Despite the benefits of these prevention methods, they are associated with many disadvantages, which highlight the need for further treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, men suffer from greater morbidity and mortality post-fracture compared to women [5,6]. They are also less likely to receive osteoporosis treatment compared women after a bone fracture [7].…”
Section: Introductionmentioning
confidence: 99%